IDENTIFICATION OF AGRICULTURAL SECTOR LEADING COMMODITIES IN MAGELANG DISTRICT - Danta Paramartha; Mukson Mukson; Budi Adi Kristanto (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2020)
Determination of leading commodities is needed to know the potential and prospective commodities that can be developed in an area. Leading commodities are expected to provide greater revenue compared to other commodities. This study aims to determine the leading agricultural subsector that has the potential to be developed as a driver of the economy in Magelang District. and analyze the trends in the growth patterns of subsector and leading agricultural commodities in the district. The method used in this study is descriptive method. The data used is time series data, namely secondary data from the GRDP of Magelang and Central Java Provinces in 2013-2017 and data on the amount of agricultural commodity production over a 7-year period (2011-2017). Data analysis tools used are Analysis of Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Klassen Typology Analysis.The results of the study shows that, horticultural plants, livestock, forestry and natural resources are base / leading subsectors of agricultural sector in Magelang District. The pattern and structure of the growth of the food crop subsector is among those that are rapidly developing, while the horticulture and livestock are among the advanced but depressed subsectors and the most advanced and fast growing food crops are sweet potatoes. On the other hand, the fast-growing group of horticultural commodities of vegetables are cabbage, cayenne pepper, tomatoes, cauliflower, cucumber, scallion, and carrots, whereas horticultural commodities in advanced and fast-growing fruit groups are rambutan and salak. In addition, the rapidly growing livestock commodities are cows, buffaloes, pigs, native chickens, and ducks. Finally the advanced but depressed commodities are goats and broilers.